Flora of kurgans in the forest steppe zone in Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
The results of study of floristic diversity of kurgans in the forest steppe zone in Poltava, Cherkasy and Kirovograd Regions, are presented. Twenty-five kurgans of more than 3 m high distributed over an area approx. 12092,4 km2, were surveyed. Being estimated at 460 species, the investigated kurgan flora contains more species than the flora of the barrows in each of the 3 steppe zones. The number of species on a single kurgan varied from 85 to 159, with 107,5 in average. As in the Pontic herb(-rich) grass steppe zone, hemicryptophytes dominated in the flora of the kurgans (39,4%) in the forest steppe zone, whereas therophytes prevailed in the barrow flora in the steppe zones southwards. Phanerophytes were more numerous as well (10,0%). Short-living plants (one, two or three years old) constituted 33,1% of the kurgan flora in the forest steppe zone. Most of them are synanthropic species, e.g. weeds from the surrounding fields. The total number of alien species (anthropophytes) reached 112. Archaeophytes and kenophytes comprised 13,7% and 7,6% of the kurgan flora. A total of 20 syntaxa of a higher rank were represented in all the kurgans studied. Species associated with steppe syntaxa such as: Festuco-Brometea, Festucetea vaginatae, Polygono-Artemisietea and Galietalia veri comprised as much as 49,3% of the kurgan flora. As in the desert and grass steppes, species belonging to classes Festuco-Brometea and Stellarietea mediae were predominant in the forest steppe as well, which also confirmed the semi-natural character of the kurgan flora. A total of 5 classes of tree and shrub communities were represented on the kurgans in the forest steppe zone: Querco- Fagetea, Urtico-Sambucetea, Robinietea and Salicetea purpureae. The number of species of particularly high floristic value was estimated at 47. The investigations carried out in the forest steppe zone confirm that kurgans constitute refugia for the steppe flora. They could play an important role in the local restoration of the natural plant cover. Therefore, they should be put under protection both as archeological and nature monuments.
Keywords: barrows, refugia of steppe flora, floristic diversity, forest steppe, protection of kurgans, Poltava, Cherkasy, Kirovograd Region, Ukraine.